Synthesis of mesoporous silica-coated magnetic nanoparticles modified with 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole and its application as Cu(II) adsorbent from aqueous samples - Wondracek, Marcos Henrique P. [UNESP]; Jorgetto, Alexandre Oliveira [UNESP]; Silva, Adrielli Cristina P. [UNESP]; Ivassechen, Janaíne Do Rocio [UNESP]; Schneider, José Fabián; Saeki, Margarida Juri [UNESP]; Pedrosa, Valber Albuquerque [UNESP]; Yoshito, Walter Kenji; Colauto, Fabiano; Ortiz, Wilson A.; Castro, Gustavo Rocha [UNESP] (Elsevier, 2016)
This study presents an alternative, rapid, and environment-friendly synthesis procedure of a magnetic core-shell mesoporous SBA-15 silica composite, its functionalization with 4-amino-3-hydrazino-5-mercapto-1,2,4-triazole (Purpald), and its application in dispersive solid-phase microextraction (DSPME) for Cu(II) from water. The materials were characterized through magnetization measurements, scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HR-TEM), Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR) of 29Si and 13C, elemental analysis, and surface area measurements. FTIR and NMR analyses indicated the presence of the ligand on the functionalized material and that it was coupled through a C-S bond. TEM images clearly show that the magnetite core particles were effectively coated with a silica shell. The material presented a surface area of 287.99 m2 g-1 and an average pore diameter of approximately 15.1 nm. The material had its point of zero charge (PZC) determined (6.17) and its adsorption capacity was evaluated as a function of time, pH, and metal concentration. Dynamic adsorption equilibrium was reached in 120 min, and it had a good correlation with the pseudo-second-order kinetic model (r2 = 0.9997). The maximum experimental adsorption capacity (0.0786 mmol g-1) and the value calculated by the linearized Langmuir model (0.0799 mmol g-1) are very approximate, indicating the formation of a monolayer over the material. Furthermore, the material proved to be very stable, because their adsorption capacity remained greater than 95% even after 10 cycles of adsorption/desorption. A high enrichment factor of 98.1-fold was observed, indicating that this material is suitable for the preconcentration of trace Cu(II) ions before analysis through flame atomic absorption spectrometry (FAAS).
Keywords: Adsorption models; Aqueous samples; Preconcentration; Solid-phase extraction